Menerapkan Budaya Literasi Sejak Dini di Tingkat Pendidikan Taman Kanak-kanak - Regina Yulianti Sabtina; Zahra Kartika Fauziyah (Pusat Riset dan Inovasi Nasional, 2023)
This article aims to implement a culture of literacy to children starting from an early age. This is due to the rise of the digital era which makes people, especially children, choose to spend more time playing gadgets. Therefore, at this time there is a lot of degradation of insight and knowledge due to lack of motivation to familiarize themselves with reading literacy. If a culture of literacy is not applied from an early age, this will cause the possibility of interest in reading and writing for the next generation to be minimal or reduced. Therefore, an understanding of literacy culture from an early age needs to be instilled because at that age, the age of the child is stepping on the